Проблемы эксплуатации высокотемпературных элементов энергетического и промышленного оборудования - Мороз, Олег Сергеевич (НТУ "ХПИ", 2018)
Представлены результаты исследований формирования и влияния профиля температур на напряженно-деформированое состояние элементов промышленного и энергетического оборудования. В качестве исследуемого элемента котлоагрегатов был выбран патрубок внутри которого протекала вода для охаждения. Рассмотрено влияние распределения температуры внутри патрубка на его напряжонное состояние. В качестве средства расчета была использована универсальная программная система конечно-элементного анализа ANSYS.

The repair rate of the energy and industrial boiler equipment is defined to a great extent by the characteristics of temperature field on the boiler tube surface. Actually, the deviation of gas temperature field from the design profile is always observed for different equipment elements when the available burner devices mainly of a registered type are working. It results in considerable thermal strains in some equipment elements and as a consequence in increased total strain. In some cases the gas temperature field nonuniformity prompts to drop the torch temperature by an increase in the excess air coefficient, decreasing thus the power plant efficiency. This scientific paper gives consideration to formation processes of the temperature field of combustion products along the chamber length and on the surface of the element of boiler equipment that was represented as a branch pipe. It was shown that the temperature profile of combustion products along the branch pipe height specified by equipment operation conditions affects the stress-strain state. It was noted that that the air and combustion product mixing process in the space between the stabilizers is characterized by a high intensity due to a high temperature gradient in the trace cross-section. However, a total equalization of the temperature gradient before the branch pipe fails to take place due to a high flow velocity. For the option studied, the highest stress was registered at the end side of branch pipe.
Problems of the usability of high-temperature elements of the energy and industrial equipment
Keywords: поле температур; патрубок; напряженно-деформированное состояние; зона обратных токов; temperature field; branch pipe; stress-strain state; reverse current zone